Aboriginal Territories in Cyberspace - Lewis, Jason E.; Fragnito, Skawennati T. (Cultural Survival Quarterly., 2005)
Indigenous peoples are making their own spaces online, using art as the backdrop for cross-cultural dialogue. Cyberspace—the websites, chat rooms, bulletin boards, virtual environments, and games that make up the internet—offers Aboriginal communities an unprecedented opportunity to assert control over how we represent ourselves to each other and to non-Aboriginals. This article introduces the concept of Aboriginally determined territories in cyberspace and discusses how these can be defined, maintained, and expanded. We will do this within the Canadian context, though much of the discussion is pertinent to Aboriginal communities in other parts of the world. We draw on lessons learned from creating and curating CyberPowWow, an Aboriginally determined online gallery, to propose Aboriginal Territories in Cyberspace, a series of initiatives to expand Aboriginal presence online. These include expanding CyberPowWow into an ongoing community of new media artists addressing Aboriginal issues; developing Skins, a project in which elders work with youth to explore tribal stories through the use of online virtual environments; and laying the foundations for Within Reservations, which will function as a blueprint for equipping Aboriginals for full participation in the ongoing revolution in networked information technologies.
Place: Cambridge, Mass. OCLC: 109435875
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Section: 215 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Section: xvii, 195 pages : illustrations en couleur ; 22 cm
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé